ACTUAL ASPECTS OF IMPLEMENTATION OF INDUSTRIAL POLICY IN PETROCHEMICAL COMPLEX - N. Volkova; A. Naboychenko (Вестник университета)
The article reflects the main problems of modern development in Russian economy and improves its competitiveness. It substantiates the importance of industrial policy and its components in a new format of economic growth. In the article were analysed the directions of industrial policy, which should be considered when choosing the priority development strategies of petrochemical companies. In addition, software measures to improve industrial policies that ensure sustainable development of the industry were proposed.